STUDENT'S IMAGE AND SEX - Basco, L. (Modern Psychology, 2020)
Research approaches the topic of the ratios women/men through the representations, which the students have of their persons. Methodology proposes initially to 7 male students and 7 female students to inform a blazon starting from six instructions in Avignon Université France. This method will allow a true analysis of Oneself. After inviting the student to an individual and personal reflection (simple autoconfrontation), cross exchanges in autoconfrontations will be led. This research will make it possible to understand : how and why variations can be raised in the reception of the representations of the image of the student as a person according to the gender in France? Starting from the various speeches given by the students and raised by the researchers, a work of both analysis and synthesis will make it possible to consider several levels of variations.
Keywords: Student, gender, self-representation, picture, blazon.